Metal-metal interactions in dinuclear (triphos)cobalt complexes exhibiting mixed valency - Heinze, Katja; Huttner, Gottfried; Walter, Olaf (European journal of inorganic chemistry, 1999)
The spectroscopic and electrochemical properties of a series of dinuclear mixed‐valence complexes containing two (triphos)Co units are reported: [(triphos)Co(L)Co(triphos)]+ (L = C6O4X2; × = H, Cl, Br,...